Cross-validation of chemical and genetic disruption approaches to inform host cellular effects on Wolbachia abundance in Drosophila - Sharmin, Zinat; Samarah, Hani; Aldaya Bourricaudy, Rafael; Ochoa, Laura; Serbus, Laura Renee (Frontiers in Microbiology, 2024)
Endosymbiotic Wolbachia bacteria are widespread in nature, present in half of all insect species. The success of Wolbachia is supported by a commensal lifestyle. Unlike bacterial pathogens that overreplicate and harm host cells, Wolbachia infections have a relatively innocuous intracellular lifestyle. This raises important questions about how Wolbachia infection is regulated. Little is known about how Wolbachia abundance is controlled at an organismal scale. This study demonstrates methodology for rigorous identification of cellular processes that affect whole-body Wolbachia abundance, as indicated by absolute counts of the Wolbachia surface protein (wsp) gene. Candidate pathways, associated with well-described infection scenarios, were identified. Wolbachia-infected fruit flies were exposed to small molecule inhibitors known for targeting those same pathways. Sequential tests in D. melanogaster and D. simulans yielded a subset of chemical inhibitors that significantly affected whole-body Wolbachia abundance, including the Wnt pathway disruptor, IWR-1 and the mTOR pathway inhibitor, Rapamycin. The implicated pathways were genetically retested for effects in D. melanogaster, using inducible RNAi expression driven by constitutive as well as chemically-induced somatic GAL4 expression. Genetic disruptions of armadillo, tor, and ATG6 significantly affected whole-body Wolbachia abundance. As such, the data corroborate reagent targeting and pathway relevance to whole-body Wolbachia infection. The results also implicate Wnt and mTOR regulation of autophagy as important for regulation of Wolbachia titer.